Doctors with dyslexia: strategies and support. (6th October 2016) - Locke, Rachel; Alexander, Gail; Mann, Richard; Kibble, Sharon; Scallan, Samantha
Summary: Background: Looking beyond dyslexia as an individual doctor's issue requires adjusting a working environment to better serve the needs of doctors with dyslexia. With an increasing number of doctors disclosing dyslexia at medical school, how can educators best provide this support? Our research looks at the impact of dyslexia on clinical practice and the coping strategies used by doctors to minimise the effect. Methods: Qualitative data were collected from 14 doctors with dyslexia using semi‐structured interviews and by survey. ' In situ ' demonstration interviews were conducted in order to understand how dyslexia is managed in the workplace from first‐hand experience. Employers and educators who have responsibility for meeting the needs of this group were also consulted. Results: Even in cases of doctors who had a diagnosis, they often did not disclose their dyslexia to their employer. Study participants reported having developed individual ways of coping and devised useful 'workarounds'. Support from employers comes in the form of 'reasonable adjustments', although from our data we cannot be sure that such adjustments contribute to an 'enabling' work environment. Supportive characteristics included the opportunity to shadow others and the time and space to complete paperwork on a busy ward. How can educators best provide support [for doctors with dyslexia]? Discussion: Doctors with dyslexia need to be helped to feel comfortable enough to disclose. Educators need to challenge any negative assumptions that exist as well as promote understanding about the elements that contribute to a positive working environment. As a result of the research there is now practice available for educators to identify evidence‐based strategies and resources.